Efektivitas Kelompok Sebaya Terhadap Perkembangan Perilaku Siswa Sekolah Dasar - Mustikaati, Wina; Nurista, Annisa Salsabila; Yudistira, Chantika Putri; Oktaviani, Mutia; Aulia, Sabrina Shafa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Peer groups play an important role in the process of individual growth and development, especially during childhood and adolescence. Although peer influence is often considered dominant, research shows that parents still have a significant impact on a child’s development. However, when relationships in the family are not harmonious, children tend to seek emotional support from peers, which can lead to involvement in negative groups such as gangs. Peer groups can have a positive impact, such as controlling behavior, providing emotional support, and developing social skills. However, negative impacts also emerge, such as discrimination against non-members of the group and disputes with parents. To improve the effectiveness of peer groups, the peer tutoring method is proposed as a learning strategy that engages students who are more capable of helping their peers. This method not only facilitates the understanding of the subject matter, but also strengthens students’ social relationships and interpersonal skills. With the right approach, adolescents can be directed to develop positively, so that their potential can grow optimally.